2004
DOI: 10.1159/000074837
|View full text |Cite
|
Sign up to set email alerts
|

Calcitriol Increases Burst-Forming Unit-Erythroid Proliferation in Chronic Renal Failure

Abstract: Background: Calcitriol (C) improves anemia in chronic renal failure. This effect may be related to the suppression of iPTH release, or to a direct effect on erythropoiesis. Methods: Thirty-three patients with chronic renal failure were enrolled; among them, 24 were on chronic hemodialysis and 9 on conservative management. None had other chronic or hematological disease, aluminum levels were below 20 µg/l and DFO testing was negative. The iPTH range was 250–480 pg/l. None were treated with C or r-HuEpo. In vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
65
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 9 publications
2
65
0
1
Order By: Relevance
“…The role of vitamin D metabolism has also been involved in the improvement of erythropoiesis by a direct effect on erythroid precursor proliferation (31) and/or, marginally, by controlling secondary hyperparathyroidism (32). In our study, the dosage of the erythroid-stimulating agent was reduced, with no modification of hemoglobin values.…”
Section: Discussionmentioning
confidence: 57%
“…The role of vitamin D metabolism has also been involved in the improvement of erythropoiesis by a direct effect on erythroid precursor proliferation (31) and/or, marginally, by controlling secondary hyperparathyroidism (32). In our study, the dosage of the erythroid-stimulating agent was reduced, with no modification of hemoglobin values.…”
Section: Discussionmentioning
confidence: 57%
“…Only one prior RCT reported on ESA dose; it found a reduction in ESA but was a very small (n=22) and unblinded study. 24 Reduced expression of proinflammatory cytokines is the proposed mechanism by which nutritional vitamin D is hypothesized to affect erythropoiesis, 13 although convincing evidence of a role for nutritional vitamin D in mediating inflammation in a manner that impacts on clinical outcomes remains to be demonstrated. 28,29 Prior RCTs that have measured inflammation in patients on hemodialysis after vitamin D supplementation have not found reductions in cytokines or T-cell or monocyte mediators.…”
Section: Discussionmentioning
confidence: 99%
“…6 A reduction in ESA dose has been found in nonrandomized trials of nutritional vitamin D supplementation in patients on hemodialysis, [6][7][8] and cross-sectional studies show an inverse relationship between serum 25(OH)D and hemoglobin and ESA dose. [9][10][11][12] In vitro and in vivo studies under conditions of vitamin D deficiency have demonstrated increased erythropoeisis with addition of vitamin D. 13,14 The postulated mechanism for nutritional vitamin D's effect is via the suppression of cytokines inhibitory to erythroid progenitors. 14 Increased availability of iron through suppression of hepcidin may also play a role.…”
mentioning
confidence: 99%
“…Calcitriol has been shown to have a direct proliferative effect on erythroid burst-forming units, and this effect is synergistic with epoetin [31]. Calcitriol also augments cultured stem cell proliferation alone and in the presence of supraphysiologic doses of epoetin [32].…”
Section: Discussionmentioning
confidence: 99%